The Role of The School Principal in Developing Students' Character Through Scouting Extracurricularies in Pringapus State Elementary School 03 - Yunanton, Didie; Rasiman, Rasiman; Sumarno, Sumarno (Al Hikmah: Journal of Education, 2024)
This research aims to explore the role of the principal as a manager in a discipline, self-confidence and responsibility character development program, the role of the principal as an educator in a character development program through positive activities, and the role of the principal as innovator in creating an environment that supports character development. The method used is descriptive qualitative, with research subjects including school principals, Head of the Curriculum Development Team, student affairs, and teachers. Primary data sources were collected through interviews and direct observation, while secondary data was obtained from supporting documents. Data collection techniques include interviews, documentation and observation. Data analysis was carried out using a qualitative descriptive analysis model which includes data collection, data reduction, data presentation and drawing conclusions. Triangulation techniques were used to validate research results. The results of the research show that the role of the principal as a manager in the character development program is seen in the effective implementation of character development program management, the role of the principal as an educator is demonstrated by the integration of positive character values into scout activities, and the role of the school principal as an innovator in personnel development, providing supporting facilities, and structuring procedures that facilitate the development of student character.